On the exact explicit solutions and conservation laws of the generalized (3+1)-D Camassa–Holm–Kadomtsev–Petviashvili equation with power law nonlinearity - Thokozani Blessing Shiba; Khadijo Rashid Adem (Partial Differential Equations in Applied Mathematics)
This study examines the Camassa–Holm–Kadomtsev–Petviashvili equation with power law nonlinearity in (3+1)-D. The highlighted equation appears in mathematical physics, particularly in the study of nonlinear optics, plasma, integrable systems, and soliton theory, among other areas. The integration of the underlying equation is done using Lie symmetry analysis. To get more precise answers, the ansatz approach is applied. Traveling wave solutions are then obtained. The multiplier approach will be used to obtain conservation laws for the underlying equation.